2020
DOI: 10.3389/fphys.2020.00280
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Paneth Cells in Extra-Intestinal Mucosal Niche Indicate a Link to Microbiome and Inflammation

Abstract: Paneth cells are residents of the intestinal epithelium. Abnormal appearance of Paneth cells has been widely documented in non-intestinal tissues within the digestive tract and even observed in non-gastrointestinal organs. Although metaplastic Paneth cells are part of the overarching pathology of intestinal metaplasia (IM), only a fraction of intestinal metaplastic lesions contain Paneth cells. We survey literature documenting metaplastic Paneth cells to gain insights into mechanism underlying their etiologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 135 publications
0
26
0
Order By: Relevance
“…Metaplastic Paneth cells are not a common feature of intestinal metaplasia. 29 Considering our patients developed this severe metaplasia at as early as 2 months of age, this feature highlights the overall unique phenotype of these patients.…”
Section: Discussionmentioning
confidence: 54%
“…Metaplastic Paneth cells are not a common feature of intestinal metaplasia. 29 Considering our patients developed this severe metaplasia at as early as 2 months of age, this feature highlights the overall unique phenotype of these patients.…”
Section: Discussionmentioning
confidence: 54%
“…Abnormalities in Paneth cell lysozyme granules and secretory defects were reported in CD patients (Liu et al, 2017;VanDussen et al, 2014) and in mice carrying CD susceptibility alleles (Bel et al, 2017). In UC, metaplastic Paneth cells in left colon are a feature of this disease (Singh et al, 2020;Tanaka et al, 2001). We found that these metaplastic Paneth cells expressed lysozyme.…”
Section: Discussionmentioning
confidence: 49%
“…Whereas Paneth cells are absent in rodent colonic epithelium, these cells are normally present in human cecum and ascending (i.e., right) colon. However, they are rarely found in human descending colon and rectum, and Paneth cell metaplasia in this region is a hallmark of IBD pathology (Singh et al, 2020;Tanaka et al, 2001). Clinical studies demonstrated a correlation between aberrant lysozyme production and IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our results, it will be interesting to investigate whether RIP140 might play a role in this pathology. Moreover, further studies will be needed to determine if RIP140 could also play a role in the PC metaplasia associated with the detection of PC-like cells at the base of colonic crypts in inflammatory cecum and right colon [49,50]. In addition, PCs provide support to stem cells by secreting EGF, Wnt3a, and DLL4, while under injury conditions, PCs acquire stem features and generate all type of intestinal epithelial cells by activating Notch and Wnt signals [51].…”
Section: Discussionmentioning
confidence: 99%